Prevalence of important poisoning methods used in Iranian suicides: A systematic review and meta-analysis - Zeinab Bidel (Majallah-i ̒Ilmī-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Simnān, 2013)
Introduction: One of the most important subjects in the study of suicide is the methods of suicide. There is not accurate information relating to employed poisoning methods for suicide in Iran. Studies conducted in different provinces provided different results. This study aimed to estimate the prevalence of poisoning methods used in attempted suicides in Iran.Materials and Methods: Domestic scientific databases, PubMed, Science direct/ISI and Scopus searched without any time limitation. Searching was updated by March 20, 2012. Initially, 1398 articles were retrieved. After review of titles, 34 studies included for review of full text. Finally, 19 articles entered in meta-analysis. Random effects model of Mantel-Haenzel employed for estimation of pooled prevalence. Meta-regression and Subgroup analyses were employed to assess the cause of heterogeneity among the selected studies.Results: This meta-analysis included 8494 males and 13503 females. Heterogeneity measure for drug poisoning and agricultural poisoning was 99.3% and 98.1%, respectively. The prevalence of drug poisoning was 75% (CI 95%: 68 to 82%) and the prevalence of agricultural poisoning was 13% (CI 95%: 10 to 16%). The lowest prevalence of drug poisoning and agricultural poisoning was in Ilam and Khorasan Razavi provinces and highest in Golestan and Ilam provinces, respectively.Conclusion: Drug poisoning was the most prevalent method for suicide. Therefore, training for no storage of drugs at home and impose more strict instructions for medications prescription are recommended.